Associations between β-Blocker Therapy at Discharge and Long-Term Follow-Up Outcomes in Patients with Unstable Angina Pectoris - Lei Liu; Xiaosong Ding; Hui Chen; Weiping Li; Hongwei Li (Cardiology Research and Practice)
Background. The effects of β-blockers in patients with unstable angina pectoris (UAP) are unclear. We tried to evaluate associations between β-blockers in UAP and long-term outcomes. Methods. We enrolled 5591 UAP patients and divided them into 2 groups based on β-blockers at discharge: 3790 did β-blockers and 1801 did not used them. Propensity score matching at 1 : 1 was performed to select 1786 patients from each group. The primary endpoint was major adverse cardiac and cerebral events (MACCE) during the long-term follow-up period. Results. 67.8% of patients were on β-blockers at discharge; these patients were more likely to have CHD risk factors, lower ejection fraction, and severity of the coronary artery lesions. Over a median of 25.0 years, the incidence of MACCE was 25.5%. The risk was not significantly different between those on and those not on β-blocker treatment. The multivariate Cox regression analysis showed that no β-blocker use at discharge was not an independent risk factor for MACCE and sequence secondary endpoints. After propensity score matching, the results were similar. Conclusions. β-blocker use was not associated with lower MACCE and other secondary composite endpoints in long-term outcomes. This result adds to the increasing body of evidence that the routine prescription of β-blockers might not be indicated in patients with UAP. Trial registration had retrospectively registered.